2009
DOI: 10.1200/jco.2009.23.8592
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Concurrent Radiation and Weekly Cisplatin Followed by VIPD Chemotherapy in Newly Diagnosed, Stage IE to IIE, Nasal, Extranodal NK/T-Cell Lymphoma: Consortium for Improving Survival of Lymphoma Study

Abstract: Patients with newly diagnosed, stages IE to IIE, nasal ENKTL are best treated with frontline CCRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
263
3
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(288 citation statements)
references
References 25 publications
15
263
3
7
Order By: Relevance
“…With a novel risk stratification and more accurate staging methods, including improved imaging techniques and molecular markers, [35][36][37] future research should aim to determine whether these patients at high risk of systemic failure can benefit from innovative, more effective systemic therapies, such as new chemotherapeutic regimens and molecular targeted therapies. [38][39][40][41] The incidence of CNS involvement was largely diverse, mainly depending on the pathological subtype and stage of NHL. 42,43 Similarly to another study, 44 we found a very infrequent CNS relapse (1%) in patients with early stage nasal NK/T-cell lymphoma, not justifying the use of CNS chemoprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…With a novel risk stratification and more accurate staging methods, including improved imaging techniques and molecular markers, [35][36][37] future research should aim to determine whether these patients at high risk of systemic failure can benefit from innovative, more effective systemic therapies, such as new chemotherapeutic regimens and molecular targeted therapies. [38][39][40][41] The incidence of CNS involvement was largely diverse, mainly depending on the pathological subtype and stage of NHL. 42,43 Similarly to another study, 44 we found a very infrequent CNS relapse (1%) in patients with early stage nasal NK/T-cell lymphoma, not justifying the use of CNS chemoprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…However, detailed information about the inclusion criteria, RT planning, and rationale for estimated sample size was not reported, although the researchers stated that these two studies had been conducted prospectively [11].…”
Section: Prospective Clinical Trials For Newly Diagnosed Localized Namentioning
confidence: 99%
“…To explore a more effective therapy for localized nasal NKTCL, prospective clinical trials of concurrent chemoradiotherapy incorporating chemotherapies with non-MDR-related agents and etoposide, which is effective against EBV-associated hemophagocytic syndrome [35], have been initiated in Japan [10] and soon after in Korea [11]. Figure 1 illustrates the protocol treatment of the two trials.…”
Section: Prospective Clinical Trials For Newly Diagnosed Localized Namentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies using simultaneous chemoradiotherapy42, 43, 44, 45 and 3 assessing chemotherapy followed by RT46, 47, 48 had ORRs of 78% to 96%, 2‐year OS rates of 78% to 88%, and 3‐year OS rates of 54% to 86%. The newly diagnosed patients in our study had an ORR of 88% and a 2‐year OS rate of 84%.…”
Section: Discussionmentioning
confidence: 99%